A Qualitative Descriptive Study of Social Media as a Means of Exchanging Public Information on the @Jogmfs Twitter Account - Lestari, Rani Dwi; Gunawan, Martin; Yusfiarista, Erlika (PT FORMOSA CENDEKIA GLOBAL, 2025)
Social Media has become ubiquitous in society, with nearly everyone, regardless of their generation or background, having a presence on various platforms. This aligns with the reality that contemporary society already employs social media as a means to distribute knowledge. There is a consensus that social media facilitates rapid, accurate, and efficient work. Social media platforms offer a rapid means of communication and information dissemination. The objective of this study is to ascertain the utilisation of Twitter, a specific form of social media, as a platform for the dissemination of public information through the Twitter account @Jogmfs. A menfess account is a specific sort of account that allows followers to send tweets automatically through the associated Twitter account. Additional followers are welcome to offer replies, reactions, or further inquiries. This study is a qualitative descriptive research that was conducted using data obtained from interviews and a survey of existing literature. This study use Regina Luttrell's SoMe theory as a research instrument. The research findings indicate that individuals in Jogja who follow the Twitter account @jogmfs perceive Twitter as an efficient platform for exchanging information about Yogyakarta. However, it should be noted that in certain circumstances, irrelevant material is also transmitted through this Twitter account.